PENILAIAN KERENTANAN PANTAI DI WILAYAH PESISIR KABUPATEN TUBAN TERHADAP ANCAMAN KERUSAKAN - Marita Ika Joesidawati (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2016)
Analisa Kerentanan Pantai ini dilakukan di wilayah pesisir pantai utara Jawa Timur khususnya Kabupaten Tuban dengan panjang pantai 65 km. Penelitian ini bertujuan untuk mengembangkan metode pengolahan data penginderaan jauh untuk penentuan parameter terkait CVI (Coastal Vulnerability Index) terhadap ancaman kerusakan dan untuk mengetahui tingkat kerentanan pantai yang diperlukan untuk merumuskan langkah-langkah mitigasi dalam meminimalkan dampak kerusakan pantai. Langkah dari penelitian ini adalah untuk mengumpulkan hidro-oseanografi dan data geologi dan informasi dari kerusakan pesisir dari data sekunder dan survey lapangan secara langsung. Pemanfaatan data penginderaan jauh dari satelit sensor optis serta sistem informasi geografis dapat memberikan informasi spasial sebagian besar parameter-parameter yang diperlukan dalam perhitungan Indeks Kerentanan Pantai. Parameter indeks kerentanan pantai (Coastal Vulnerability Index/CVI) yang digunakan dalam pembobotan Kerentanan pantai terhadap ancaman kerusakan menggunakan 10 variabel fisik pantai, yaitu: (1). Geomorfologi pantai (GF), (2) Ketinggian Permukaan Tanah (Elevasi/E), (3) Tunggang pasut (Tidal Range) rata-rata (TR),(4) Tinggi Gelombang Signifikan (SHW) (5) Kenaikan Muka Air Laut Relatif (SLR), (6) Perubahan Garis Pantai (PGP), (7) Penggunaan Lahan (PL), (8) Litologi (L), (9) Luas Kerusakan Pantai (KP), (10) Lebar sabuk hijau (SH). Pengelompokan kelas dilakukan dengan membaginya berdasarkan persen dengan kisaran antar kelas 20%. Nilai yang kurang dari sama dengan 20% termasuk kelas tidak rentan, 20% – 40% termasuk dalam kelas kurang rentan, 40% – 60% kelas sedang, 60% – 80% masuk dalam kelas rentan, dan lebih dari 80% masuk kelas sangat rentan. Berdasarkan hasil survey, perhitungan dan analisa terhadap seluruh data, diperoleh nilai CVI wilayah pesisir pesisir utara Kabupaten Tuban yang terdiri dari 5 Kecamatan pantai dikelompokkan menjadi 4 kategori kerentanan terhadap ancaman kerusakan, yaitu: kerentanan sangat tinggi (220-275), kerentanan tinggi (165-220), kerentanan sedang (110-165), dan kurang rentan (55-110). Kecamatan Bancar termasuk dalam 4 kategori yaitu kurang rentan sampai sangant rentan, Kecamatan Jenu termasuk daerah yang rentan dan sangat rentan, Kecamatan Palang dan Tambakboyo pada kategori sedang sampai sangat rentan, sedangkan Tuban termasuk pada daerah sedang dan rentan.Kata Kunci : kerentanan pantai, CVI, Inderaja dan SIG, ancaman kerusakan VULNERABILITY ASSESSMENT OF TUBAN DISTRICT COASTAL AREAS TO THE DAMAGING THREAT Coastal Vulnerability analysis was conducted in the northern coast of East Java, especially in Tuban with a coastline ca. 65 km. This research aims to develop remote sensing data processing method for the determination of parameters related to CVI (Coastal Vulnerability Index) against the damaging threat and to determine the level of vulnerability of the coast needed to formulate mitigation measures to minimize the impact of damage to the beach. Steps of this research is to collect oceanographic and hydro-geological data and information from damaged coastal from secondary data and field survey. Utilization of remote sensing data from satellites as well as the optical sensor geographic information systems can provide spatial information most of the parameters required in the calculation of Coastal Vulnerability Index. Parameter of coastal vulnerability index (CVI) that is used in weighting the beach Vulnerability to threats of physical damage using 10 variables, namely: (1). Coastal geomorphology (GF), (2) Elevation (E), (3) Stables tide (Tidal Range) Average (TR), (4) Significant Wave Height (SHW) (5) Sea Level Rise relative (SLR), (6) Changes in Coastline (PGP), (7) Land Use (PL), (8) lithology (L), (9) area of Damage Coast (KP), (10) The width of the green belt (SH). Grading is done by dividing by percent with a range between 20% grade. Values less than or equal to 20%, classes as is not vulnerable, 20% - 40% is included in the class of less susceptible, 40% - 60% of the classes of moderately vulnerable, 60% - 80% as classes vulnerable, and over 80% go to class very susceptible. Based on survey results, calculation and analysis of all data obtained CVI value of coastal areas north coast of Tuban consisting of 5 Districts beach grouped into four categories of vulnerability to the threat of damage, namely: very high susceptibility (220-275), high susceptibility (165 -220), moderate susceptibility (110-165), and less susceptible (55-110). District of Bancar included in four categories: less susceptible very vulnerable, District Jenu including vulnerable areas and are moderately vulnerable, District Palang and Tambakboyo at moderate to very vulnerable category, while Tuban included in the moderate and vulnerable areas.Keywords: Coastal vulnerability, CVI, Remote sensing and GIS, Damaging threat.VULNERABILITY ASSESSMENT OF TUBAN DISTRICT COASTAL AREAS TO THE DAMAGING THREAT Coastal Vulnerability analysis was conducted in the northern coast of East Java, especially in Tuban with a coastline ca. 65 km. This research aims to develop remote sensing data processing method for the determination of parameters related to CVI (Coastal Vulnerability Index) against the damaging threat and to determine the level of vulnerability of the coast needed to formulate mitigation measures to minimize the impact of damage to the beach. Steps of this research is to collect oceanographic and hydro-geological data and information from damaged coastal from secondary data and field survey. Utilization of remote sensing data from satellites as well as the optical sensor geographic information systems can provide spatial information most of the parameters required in the calculation of Coastal Vulnerability Index. Parameter of coastal vulnerability index (CVI) that is used in weighting the beach Vulnerability to threats of physical damage using 10 variables, namely: (1). Coastal geomorphology (GF), (2) Elevation (E), (3) Stables tide (Tidal Range) Average (TR), (4) Significant Wave Height (SHW) (5) Sea Level Rise relative (SLR), (6) Changes in Coastline (PGP), (7) Land Use (PL), (8) lithology (L), (9) area of Damage Coast (KP), (10) The width of the green belt (SH). Grading is done by dividing by percent with a range between 20% grade. Values less than or equal to 20%, classes as is not vulnerable, 20% - 40% is included in the class of less susceptible, 40% - 60% of the classes of moderately vulnerable, 60% - 80% as classes vulnerable, and over 80% go to class very susceptible. Based on survey results, calculation and analysis of all data obtained CVI value of coastal areas north coast of Tuban consisting of 5 Districts beach grouped into four categories of vulnerability to the threat of damage, namely: very high susceptibility (220-275), high susceptibility (165 -220), moderate susceptibility (110-165), and less susceptible (55-110). District of Bancar included in four categories: less susceptible very vulnerable, District Jenu including vulnerable areas and are moderately vulnerable, District Palang and Tambakboyo at moderate to very vulnerable category, while Tuban included in the moderate and vulnerable areas.Keywords: Coastal vulnerability, CVI, Remote sensing and GIS, Damaging threat.